Progress in genetics of type 2 diabetes and diabetic complications. Issue 4 (14th January 2023) - Shojima, Nobuhiro; Yamauchi, Toshimasa
Abstract: Type 2 diabetes results from a complex interaction between genetic and environmental factors. Precision medicine for type 2 diabetes using genetic data is expected to predict the risk of developing diabetes and complications and to predict the effects of medications and life‐style intervention more accurately for individuals. Genome‐wide association studies (GWAS) have been conducted in European and Asian populations and new genetic loci have been identified that modulate the risk of developing type 2 diabetes. Novel loci were discovered by GWAS in diabetic complications with increasing sample sizes. Large‐scale genome‐wide association analysis and polygenic risk scores using biobank information is making it possible to predict the development of type 2 diabetes. In the ADVANCE clinical trial of type 2 diabetes, a multi‐polygenic risk score was useful to predict diabetic complications and their response to treatment. Proteomics and metabolomics studies have been conducted and have revealed the associations between type 2 diabetes and inflammatory signals and amino acid synthesis. Using multi‐omics analysis, comprehensive molecular mechanisms have been elucidated to guide the development of targeted therapy for type 2 diabetes and diabetic complications. Abstract : Genome‐wide association studies (GWAS) were conducted and new genetic loci were identified that modulate the risk of developing type 2 diabetes and diabetic complications. The polygenic risk score and multi‐omics analysis have begun to decipher the molecular mechanisms of diabetes and its complications.